Depopulation and population ageing of rural areas in Bjelovar-Bilogora county (1961-2011) - Pokos, Nenad (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
Bjelovar-Bilogora County is located in the central part of the Croatian Pannonian-Peripannonian space. In spite of good location within Croatia and favourable physiogeographical characteristics, this county was marked by very negative demographic characteristics in last fifty years. In relation to the county as a whole, the demographic situation in the rural parts is more unfavourable than in urban settlements. Between 1961 and 2011, the rural population of the county was reduced for 46.7%.
Keywords: Croatia; demografija; demografski razvoj; demography; depopulacija; Hrvaška; podeželje; prebivalstvo; rural area; staranje; staranje prebivalstva